Perbedaan Tingkat Pendidikan, Pola Asuh Ibu dan Status Gizi pada Anak Karies dan Non Karies di TK Aisyiyah Bustanul Athfal Imam Syuhodo Kabupaten Sukoharjo - Habibah, Ummu; , Susi Dyah Puspowati, S.P, M.Si; , Elida Soviana, S.Gz., M.Gizi (2017)
Caries is a disease that can damage the tooth structure. The level of education is one of factors that affects the occurrence of caries, because it will affect mothers parenting of children. Caries will have an impact on the nutritional status, because it can affect the balance between intake and output of nutrient in children. The aim of this study was to determine differences in the level of education, mothers' parenting model and nutritional status between caries and non-caries children at Aisyiyah Bustanul Athfal Imam Syuhodo Kindergarten of Sukoharjo. The study was an observational with cross-sectional design. Research subjects were 56 children aged 4-6 years and the mothers were also being respondents. Sampling method used Simple Random Sampling. Statistical tests used Mann Whitney and independent T-tests. The distributions of mothers' education level with high category were 57,15% in caries group and 82,15% in non-caries group. Distribution of mother's parenting model with good category were 42,86% in caries group and 57,14% in non-caries group. Most of the children had normal nutritional status which were 78,58% in caries group and 67,86% in non-caries group. Results of research on mothers' education level showed p value= 0,014. Mothers' parenting model showed p value = 0,019 and nutritional status resulted p value = 0,351. There were differences in the level of mothers' education and mothers' parenting model between caries and non-caries children at Aisyiyah Bustanul Athfal Imam Syuhodo Kindergarten of Sukoharjo. There was no difference in the nutritional status between caries and non-caries children at Aiyiyah Bustanul Athfal Imam Syuhodo Kindergarten of Sukoharjo.